Соціальні та політичні наслідки для України польського Січневого повстання 1863 р. - Шандра, В.С. (Український історичний журнал, 2014)
З’ясовуються конкретні заходи верховної влади Російської імперії, до яких вона
вдалася після придушення Січневого повстання 1863 р. та які було спрямовано
на подолання польської присутності в Україні, найперше у землеволодінні.
Визначаються їх наслідки у соціально-економічній, політичній, націєтворчій
та культурно-освітній площинах. In the article examined the specific measures of supreme power of the Russian
Empire, applied after the January uprising of 1863 and directed to reduction of the
polish landownership in Ukraine, as well as on expulsing of Poland from a local
government. It was found out the facilities mobilized by the Empire to be supported
by Ukrainians. Among them the lowering of redemption payments for land for the
peasants and the possibilities for the local officials to acquire it on the favorable
conditions, and also the attracting them to government service. There are also marked
the russification in the spheres of public resources policy, in education, limitation of
liberal reforms’ distribution. It is also indicated on appearance of the sociocultural
movement of khlopomania under pressing of polish movement and public policy,
with which the forming of Ukrainian language and culture and also its prohibition in 1863 were connected. It is defined that the created situation substantially slowed the formation of Ukrainian national identity.